Kemampuan Fisik Atlet Pelatda Bolabasket Kabupaten Sinjai - Ilham Kamaruddin (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2020)
ABSTRACTThe study aims to find out the physical condition of athletes the basketball trigger Sinjai. This type of research is a type of expost facto research by analyzing the physical condition of basketball athletes on Sinjai. This research was held on the district PERBASI Pengcab. Sinjai is located in Sinjai. The Instrument test used is the documentation. Its population is the entire athlete of Sinjai's basketball trigger, which amounted to 22 athletes. Samples in this study used saturated samples or total sampling and obtained as much as 22 athletes. The data analysis technique used is a descriptive analysis by classifying each test result according to the category of its physical condition. The results showed that; (1) physical condition of muscular strength of the arm and shoulder basketball athlete Sinjai is categorized well. (2) physical condition of running speed 45.73 M (50 yards) basketball athlete Sinjai is categorized as well. (3) Physical condition of muscular endurance is categorized perfectly ABSTRAKPenelitian ini bertujuan untuk mengetahui kemampuan fisik atlet Pelatda bola basket Sinjai. Jenis penelitian ini adalah jenis penelitian expost facto dengan menganalisis kemampuan fisik atlet bola basket Sinjai pada . Penelitian ini dilaksanakan pada Pengcab PERBASI Kab. Sinjai yang berlokasi di Sinjai. Instrument tes yang digunakan adalah dokumentasi. Populasinya adalah seluruh atlet Pelatda Bola Basket Sinjai yang berjumlah 22 atlet. Sampel dalam penelitian ini menggunakan sampel jenuh atau total sampling dan diperoleh sebanyak 22 atlet. Teknik analisis data yang digunakan adalah analisis deskriptif dengan mengklasifikasi setiap hasil tes sesuai dengan kategori kemampuan fisikinya. Hasil penelitian menunjukkan bahwa; (1) Kemampuan fisik kekuatan otot lengan dan bahu atlet bola basket Sinjai  di kategorikan baik. (2) Kemampuan fisik kecepatan lari 45,73 M (50 yard) atlet bola basket Sinjai  dikategorikan baik. (3) Kemampuan fisik daya tahan otot tungkai dikategorikan sempurna.